The Effect of Management Accounting Systems, Organizational Culture on Managerial Performance of Business Strategy as Moderation (Case Study At Pt. Xxx (Persero) Tbk ) - Alik Sugeng Hartanto; Enny Susilowati Mardjono (Jurnal Telekomunikasi dan Informatika, 2025)
This study aims to analyze the influence of management accounting systems and organizational culture on managerial performance, with business strategy as a moderating variable. The research was conducted at PT. XXX (Persero) Tbk, one of the leading construction companies in Indonesia. A quantitative research method with a survey approach was employed, involving 100 respondents consisting of managers and mid-level employees. Data were collected through questionnaires and analyzed using multiple linear regression and moderated regression analysis (MRA). The results indicate that the management accounting system has a positive and significant effect on managerial performance, with a coefficient of β = 0.42 (p < 0.05). Organizational culture also positively and significantly influences managerial performance (β = 0.36; p < 0.05). Furthermore, business strategy was found to strengthen the influence of both the management accounting system and organizational culture on managerial performance, with interaction coefficients of 0.18 and 0.15, respectively (p < 0.05). This research provides important contributions to the management of PT. XXX (Persero) Tbk in enhancing managerial performance through effective management of accounting systems and organizational culture. It is hoped that the findings of this study can serve as a reference for other companies facing challenges in an increasingly competitive business environment.